Градації вираження емоційної стабільності у студентів творчих спеціальностей - Прокопович, Тетяна Анатоліївна; Prokopovych, Tetiana A. (Університет " Україна", 2013)
Запропонований емпіричний матеріал презентує результати вивчення емоційної стабільності студентів творчих спеціальностей. Виявлені градації вираження емоційної стабільності містять відмінності у індивідуально-психологічних показниках досліджуваних, порівняльний аналіз яких конкретизує структуру емоційної стабільності/нестабільності творчої особистості. The gradations of the expression of emotional stability of the students of creative specialties The proposed empirical material presents the results of observation of emotional stability of students of creative professions. The identified gradations of expression of emotional stability include differences in individual psychological indicators of the examined people, comparative analysis of which specifies the structure of emotional stability / instability of the creative personality. Keywords: emotional stability / instability, creative personality, students, emotions, neuro-psychological stability.
The gradations of the expression of emotional stability of the students of creative specialties
Keywords: emotional stability; creative personality; neuro-psychological stability; emotions; емоційна стабільність; творча особистість; емоції; нервово-психічна стійкість.